Prognostic implications of high-sensitivity cardiac troponin T assay in a real-world population with non-ST-elevation acute coronary syndrome. (September 2018) - Magnoni, Marco; Gallone, Guglielmo; Ceriotti, Ferruccio; Vergani, Vittoria; Giorgio, Daniela; Angeloni, Giulia; Maseri, Attilio; Cianflone, Domenico
Abstract: Background: High-sensitivity cardiac troponin T (hsTnT) was recently approved for clinical use by the Food and Drug Administration. The transition from contemporary to hsTnT assays requires a thorough understanding of the clinical differences between these assays. Hypothesis: HsTnT may provide a more accurate prognostic stratification than contemporary cardiac troponin I (cTnI) in patients with non-ST-segment elevation acute coronary syndromes (NSTE-ACS). Methods: HsTnT and cTnI were measured in 644 patients with CK-MB negative NSTE-ACS who were enrolled in the prospective multicenter SPAI (Stratificazione Prognostica dell'Angina Instabile) study. Patients were stratified at the 99th percentile reference limit for each assay. The primary endpoint was cardiovascular death (CVD) or non-fatal myocardial infarction (MI); the secondary endpoint was the occurrence of unstable angina (UA). Follow-up lasted 180 days. Results: Patients with hsTnT ≥99th percentile were at higher risk of CVD/MI (30-day: 5.9% vs 0.8%, p = 0.001; 180-day: 11.1% vs 4.7%, p = 0.004), also after adjusting for TIMI Risk Score. No significant difference in CVD/MI at 180-day was found between hsTnT-positive/cTnI-negative and hsTnT-negative/cTnI-negative patients (adjHR 1.61, 95% CI 0.74–3.49, p = 0.232). Occurrence of UA was not differently distributed between hsTnT groups dichotomized at the 99th percentile (12.4% vs 12.5% p = 0.54). Conclusions: Our investigation on a real-world NSTE-ACS population showed good prognostic performance of hsTnT in the risk stratification of the hard endpoint, but did not demonstrate the improved prognostic ability of hsTnT over contemporary cTn. Neither troponin assay predicted the recurrence of UA, suggesting the acute rise of cardiac troponin as a marker of severity, but not the occurrence of future coronary instability.